해외금융계좌신고제도의 도입이 조세피난처 자본흐름에 미치는 영향 - 양철원; Cheol-won Yang; 조홍종; Hong-jong Cho (Seonmul yeongu (Online), 2018)
해외금융계좌신고제도는 한국인의 해외금융계좌를 통한 탈세와 불법행위를 방지할 목적으로 도입되었으며, 2010년 12월 27일 ‘국제조세조정에 관한 법률’ 안에 신설되어 이듬해인 2011년 6월 첫 신고를 받았다. 제도는 이후 2014년까지 3번의 개정을 거쳐 더욱 강화되었다. 첫 개정은 2011년 12월 31일 이루어졌으며 2012년 1월부터 적용되었다. 이후 2013년 1월과 2014년 1월에 각각 개정 및 시행되었다. 본 논문은 제도 도입 이후 전반적인 운영성과를 평가하였다. 또한 2010년부터 2014년까지 5년 동안의 한국 주식시장 자료를 통해 제도 시행과 변경이 조세피난처 투자자에 미친 영향을 분석하였다. 외국인으로 위장한 한국인이 익명성이 보장되는 조세피난처를 통해 한국 주식 거래에 참여한다고 가정하면, 본 제도는 다른 국가들보다 조세피난처 국가로부터 들어오는 자본유입을 위축시키는 방향으로 작동할 것이다. 국가별 자본흐름을 사용한 회귀분석 결과, 해외금융계좌신고제도의 도입과 강화된 제도의 시행 후에 다른 국가들에 비해서 조세피난처의 자본유입이 감소되는 결과를 발견하였다. 이는 제도의 도입과 이후 지속적인 개정을 통한 제도 강화가 유효하였음을 의미한다. The Foreign Financial Accounts Reporting was introduced for the purpose of preventing tax evasion and illegal acts through foreign financial accounts of Koreans. On December 27, 2010, it was newly established in “The Law for the Coordination of International Tax Affairs” and received its first report in June 2011, the following year. The system was further strengthened after three revisions. The first amendment was enforced from January 2012 after it took place on December 31, 2011. Thereafter, revisions and enforcement proceeded simultaneously in January 2013 and January 2014. This paper evaluates the performance of the system for four years from 2011 to 2014. In addition, we examined the effect of institutional implementation and changes on tax haven investors through empirical analysis using Korean stock market data. Assuming that Koreans disguised as foreigners participate in Korean stock trading through an anonymity of tax haven, this system will work to shrink the flow of capital from tax haven investors to other countries. Panel regression analysis using capital flows by country found that the transaction activity of tax havens decreased as compared to other countries after introducing and strengthening the acts.